Enhanced Osteogenesis of Adipose-Derived Stem Cells by Regulating Bone Morphogenetic Protein Signaling Antagonists and Agonists. (8th March 2016) - Fan, Jiabing; Im, Choong Sung; Guo, Mian; Cui, Zhong-Kai; Fartash, Armita; Kim, Soyon; Patel, Nikhil; Bezouglaia, Olga; Wu, Benjamin M.; Wang, Cun-Yu; Aghaloo, Tara L.; Lee, Min
Abstract : The direct use of adipose-derived stem cells (ASCs) alone has had limited success in the treatment of large bone defects. This study used an alternative approach that complements bone morphogenetic protein (BMP) activity to maximize the osteogenesis of ASCs by regulating levels of antagonists and agonists to BMP signaling. Findings indicate promising stem cell-based therapy for treating bone defects that can effectively complement or replace current osteoinductive therapeutics. Abstract: : Although adipose-derived stem cells (ASCs) are an attractive cell source for bone tissue engineering, direct use of ASCs alone has had limited success in the treatment of large bone defects. Although bone morphogenetic proteins (BMPs) are believed to be the most potent osteoinductive factors to promote osteogenic differentiation of ASCs, their clinical applications require supraphysiological dosage, leading to high medical burden and adverse side effects. In the present study, we demonstrated an alternative approach that can effectively complement the BMP activity to maximize the osteogenesis of ASCs without exogenous application of BMPs by regulating levels of antagonists and agonists to BMP signaling. Treatment of ASCs with the amiloride derivative phenamil, a positive regulator of BMP signaling, combined with gene manipulation to suppress the BMP antagonist noggin, significantly enhanced osteogenic differentiation of ASCs through increased BMP–Smad signaling in vitro. Furthermore, the combination approach of noggin suppression and phenamil stimulation enhanced the BMP signaling and bone repair in a mouse calvarial defect model by adding noggin knockdown ASCs to apatite-coated poly(lactic-coglycolic acid) scaffolds loaded with phenamil. These results suggest novel complementary osteoinductive strategies that could maximize activity of the BMP pathway in ASC bone repair while reducing potential adverse effects of current BMP-based therapeutics. Significance: Although stem cell-based tissue engineering strategy offers a promising alternative to repair damaged bone, direct use of stem cells alone is not adequate for challenging healing environments such as in large bone defects. This study demonstrates a novel strategy to maximize bone formation pathways in osteogenic differentiation of mesenchymal stem cells and functional bone formation by combining gene manipulation with a small molecule activator toward osteogenesis. The findings indicate promising stem cell-based therapy for treating bone defects that can effectively complement or replace current osteoinductive therapeutics.